Anticipación de la actividad reproductiva en ovejas de raza Churra Galega Bragançana - efecto de las gonadotopinas coriónicas - Valentim, Ramiro (2014)
This work aimed to assess if a pre-treatment with melatonin may improve the efficiency of a short-term progestagen treatment in advancing the breeding season in Churra Galega Bragançana ewes. The effects of eCG and hCG were also assessed. ln March, 65 adult ewes were randomly divided in two groups: 28 received a subcutaneous implant of melatonin (18 mg) as the others 37 got no treatment (Control). Forty-live days afterward all ewes were treated with an injection of 1 00 micrograms of PGF2alfa analogous and a vaginal sponge with 20 mg of FGA. Sponges were removed 5 days later. At this time, 21 Control and all Melatonin ewes were injected with 500 lU of eCG. The remaining 16 Control ewes received an injection of 500 lU of hCG. Short-term progestagen treatment was valuable in advancing the breeding activity. Exogenous melatanin did not improve the efficiency of this treatment. eCG and hCG had identical effects on fertility. Fertility rate was generally fair.